RECONSTITUTION OF SOLAR DEHYDRATED POTATO SLICES AND CUBES - Rani, Manju; Ezekiel, R. (Potato Journal, 2013)
Solar dehydration of 2 and 4 mm thick slices and 1 cm cubes prepared from tubers of Kufri Jyoti was done under a temperature range of 23-28Â°C and RH range of 20-36%. Slices of 2 mm thickness took 4 h to achieve 80% weight loss whereas, 4mm thick slices took 7 h and 30 min. In the case of 1 cm cubes, 13 h and 40 min of solar dehydration were required to achieve 80% weight loss. The rate of rehydration was 450%, when 2 mm thick dehydrated slices were soaked in boiling water for 45 min. It was concluded that potato slices can be solar dried, stored and utilized in two ways. They can be fried when needed and consumed as chips or they can be reconstituted by soaking in boiling water for 15-30 minutes, mashed and used during summer months when the price of potatoes is quite high. Reconstitution of cubes was not satisfactory.